HUBUNGAN PERAWATAN PAYUDARA DENGAN PRODUKSI ASI PADA IBU NIFAS DI PUSKESMAS WINONG KEMIRI KABUPATEN PURWOREJO - Wulandari, Fetty Chandra (Jurnal Komunikasi Kesehatan, 2024)
A preliminary study conducted on June 8 2024 at the Winong Kemiri Community Health Center contained 24 postpartum mothers. Results from interviews with 6 postpartum mothers, 4 of whom stated that they had not been able to breastfeed their babies exclusively because their milk output was still small. The aim of this research was to determine the relationship between breast care and breast milk production in postpartum mothers at the Winong Kemiri Community Health Center. The research method uses a cross-sectional prospective approach. The population is 30 postpartum mothers at the Winong Kemiri Community Health Center. The sample used total sampling, namely all postpartum mothers who came to the Winong Kemiri Health Center. Candlenut. This research instrument uses a checklist. The statistical test technique uses the Chi-square test. The results of the study showed a relationship between breast care and breast milk production in postpartum mothers (p value 0.006). Keywords: Breast Care, Breast Milk Production, Postpartum Period